Microbiology : - Cowan, Marjorie Kelly. (McGraw-Hill, 2006)
Following the tradition of microbiology textbooks, the first 16 chapters o Microbiology: A Systems Approach provide the basics about microorganisms: what the are, the methods used to study them, human attempts to control them, and our bodies' defenses against them. For chapters 17-23, we have developed an unequaled level of organization in our presentation of the infectious disease material.